Trucking : A Performance Assessment Framework for Policymakers - Blancas, Luis C. (World Bank, Washington, DC, 2020)
There is a global need to better understand the inner workings of trucking markets and how these relate to performance. Despite the critical role that trucking plays as a dominant mode in most countries’ freight transport task, and as a key determinant of both private logistics costs and economic externalities, remain insufficiently understood and under-studied. This report starts from the basic definition of actors as comprising trucking service providers on the supply side, shippers and beneficial cargo owners on the demand side, and the public sector, broadly defined, on the side of the public interest that is reflected in issues of import to society at large. But it is critical to delve deeper to reflect the way trucking operations are conducted in practice, by disaggregating these main actor types into further dimensions of supply, demand, and public interest factors to arrive at a more realistic view of performance. The report is structured as follows. Chapter 1 describes the organizational structure of the trucking industry in the international experience. Chapters 3 through 5 subsequently describes the interests and typical decision-making motivations for each type of actor, and what ‘performance’ means to each of them. Chapters 5 concludes.